Financial Ratio Analysis in Assessing the Financial Performance of PT Kalbe Farma TBK for The Period 2021–2025 - Alfia Rosalinda; Fina Aulia; Milenia Hikmatu Syifa; Siti Robiatul Hadawiyah; Fadia Maulida; Herayati Herayati (PT. Anagata Sembagi Education, 2026)
This study aims to analyze the financial performance of PT Kalbe Farma Tbk. during the 2021–2025 period through liquidity, solvency, and profitability ratios. The study uses a quantitative descriptive method utilizing secondary data in the form of annual financial reports published on the Indonesia Stock Exchange. The analysis was conducted using the Current Ratio (CR), Quick Ratio (QR), Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), Return on Assets (ROA), and Return on Equity (ROE). The results show that PT Kalbe Farma Tbk. has a strong and stable financial condition. The average CR value of 414.0%, QR 254.4%, DAR 17.30%, DER 20.97%, ROA 11.60%, and ROE 14.05% reflects excellent liquidity, low debt levels, and the ability to generate consistent profits. Despite a decline in profitability in 2023, the company managed to recover in 2024–2025. These findings demonstrate the company's resilience in navigating economic dynamics in the post-COVID-19 pandemic era. This research is expected to serve as a reference for management, investors, and creditors in decision-making, while also enriching studies on the financial performance of pharmaceutical companies in Indonesia.